The Effects of Supplementing Lysophosphatidylcholine in Diet on Production Performance, Egg Quality and Intestinal Morphology of Laying Hens - Juntanapum, Witchanun; Poeikhampha, Theerawit; Poungpong, Kanokporn; Rakangthong, Choawit; Kromkhun, Pudcharaporn; Bunchasak , Chaiyapoom (International Journal of Poultry Science, 2019)
Background and Objective: This study was conducted to evaluate the effects of supplementation of Lysophosphatidylcholine (LPC) in diets on production performance, egg quality and intestinal morphology of laying hens. Materials and Methods: A total of 288 commercial laying hens (Lohmann brown-classic) from 33-46 weeks of age were used in this study. The hens were divided into 3 groups of 8 replications with 12 hens each. According to the experimental groups, hens were fed as 1) control diet, 2) control diet with 0.05% LPC and 3) control diet with 0.10% LPC. Results: At the end of the trial, supplementations of LPC (0.05 and 0.10%) significantly improved feed conversion ratio (FCR), increased egg size, decreased feed intake and reduced feed cost per egg weight (FCE) (p